Perbandingan Hasil Belajar Siswa antara Model Pembelajaran Kooperatif Tipe Team Games Tournament dengan Student Teams Achievement Division - Andi Badli Rompegading; Murniati Safitri; Rizal Irfandi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to compare student learning outcomes between those using the TGT cooperative learning model and the STAD type. The type of research used is quasi-experimental research (quasi-experimental) with Pretest-Posttest One Groups Design. The sampling technique is purposive sampling. The instrument used to determine student learning outcomes is a multiple-choice test. The results showed that the average learning outcomes of students who were taught using the TGT type cooperative learning model were 86.7, while the intermediate student learning outcomes taught using the STAD type cooperative learning model were 79.71. The results of inferential data analysis show that the significance value obtained is 5.13 > T table 2.003. In conclusion, there is a significant difference between the TGT type of cooperative learning model and the STAD type of cooperative learning model on the learning outcomes of class VII students of SMP Negeri 2 Majauleng. Keywords: Student Learning Outcomes, Student Teams Achievement Division (STAD), Team Games Tournament (TGT)